Thirty years' observations on the effects of taxing provisions instead of income . with a just scale to tax income, derived from real property /; (sold by Effingham Wilson [etc.], 1836)
This publication is a new ed. of A letter addressed to the late Earl of Liverpool, in the year 1822, ...